Att lära till man: Genusteoretiska idéer tillämpade på unga mäns inskolning i manlighet - Åström, Lissie (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1993)
The present article consists partly of a discussion of theoretical and methodological ideas of the gender problematic (which crystallized when the present author conducted her studies of male and female ways of life); and partly of a brief empirical application of these ideas to the schooling of young men in masculinity. The author discusses how prevailing principles of the sexes' behavioural and mental segregation simultaneously regulates the dominance relationship existing between them. She maintains that a culturally and socially prescribed distortion of men's and women's avenues of opportunity in what she calls a centrifugal direction (performance- and achievement-oriented) on the one hand, and a centripetal direction (welfare- and relation-oriented) on the other, has tended to generate and sustain male dominance. The empirical application offers insight into how work has served as an initiation in masculinity and as a legitimation of male superiority. In order to further illuminate how young men appropriate a typicalle male self-perception and life strategy, examples are cited which illustrate how they, in comparison to young women, are allowed greater freedom to confront life's challenges and indulge in its amusements. Class-conditioned differences are also touched upon, as well as tendencies indicating change observed over the course of three generations.